Crenças, conhecimento e ações de mães de crianças com deficiência auditiva: implicações na reabilitação - Araujo, Juliana Constantino de (2022)
Introduction: The impact on the family and the training of professionals to deal with them during this period require specific actions and training of professionals for early childhood speech therapy. Several strategies are described in the literature involving aspects of knowledge and attitudes of the family in relation to their involvement in the rehabilitation process, aiming at the greater effectiveness of auditory rehabilitation in babies and children with hearing impairment. Objective: The aim of this research is to identify the needs, knowledge, and attitudes of the family regarding their involvement in the process of auditory rehabilitation in babies and newly diagnosed children with hearing impairment. Method: The subjects of this study were seventeen children with hearing loss from 0 to 5 years old, who started the hearing aid adaptation process between 2019 and 2021 and their parents and/or guardians, in a CER II in the city of São Paulo. The measurement of the use of the AASI with the demographic characteristics of the child and his/her guardian and the Scale of Parental Involvement and self-efficacy-revised questionnaire were collected. Results: Of the total number of children, a 58.82% had an SII ≥36%. There was a tendency to use the AASI lower than ideal for the age of children who are not in therapy, for those who are not in therapy, 71.4% makes little use of the AASI, however all have SII65dB of the best ear ≤ 35%. Twelve (70.6%) reported having little belief, 8 (66.7%) use the lower ideal of the AASI and only 4 (33.3) use it close to the ideal. Only 5 (29.4%) answered having a lot of belief, being 3 (60%) use the AASI and 4 (40%) use lower than ideal. The relationships between demographic and audiological characteristics were analyzed from the perspective of parents’ perception of the knowledge, attitudes and needs reported by the parents. Conclusion: The aspects raised in the family involvement scale seemed to be determinant in the design of therapeutic goals, because they allowed the identification of values and expectations that, if worked, can strengthen the family and its availability in the participation of the therapeutic process